Sustainable energy and CO2reduction policy in Thailand: An input–output approach from production- and consumption-based perspectives - Tharinya Supasa (2018)
© 2017 International Energy Initiative Energy shortages and CO2emissions reductions are critical contemporary challenges for Thailand. A consumption-based analysis provides crucial information that enables policymakers to more comprehensively understand the hidden contributors of energy demand and CO2in the economy. The other manufacturing, construction and food and beverage sectors were amongst the five largest contributors to energy use and emissions in both 2000 and 2010, based on a consumption perspective. However, these sectors have been neglected by energy conservation and climate change mitigation policies in Thailand because they were the least energy-intensive sectors per government energy reports from 1995 to 2015. The CO2emissions burden from exports was almost 50% of Thailand's national CO2inventory in 2000 and 2010. The embodied CO2emissions results revealed that Thailand could reduce its emissions inventory by 12% and 13% if embodied imports replaced exports in 2000 and 2010, respectively. Furthermore, the leading gross domestic product-generating industries in Thailand are seriously vulnerable to natural gas and crude oil shortages despite some sectors using them in small proportions in their production processes. Energy and emissions policies should better reflect consumption characteristics to increase the potential of energy-saving interventions and CO2mitigation.